FACTORS AFFECTING ECONOMIC GROWTH IN EAST JAVA PROVINCE IN 2011 – 2020 - Hubaidillah, Ahmad; Soelityo, Aris; Kusuma, Hendra (Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to examine the analysis of the effect of general allocation funds, regional taxes, and population on economic growth in East Java Province from 2011 to 2020. Tax reforms mandated by Law number 28 of 2009 have encouraged local governments to increase equity among regions to reduce regional inequality. The variables used include general allocation funds, local taxes, and total population. Using multiple regression analysis with panel data regression for five samples of districts/cities in East Java Province, the results show that General Allocation Fund (DAU) has a positive and significant infliuence on the economic growth rate. Meanwhile Regional tax and Population has a negative and significant infliuence on the economic growth rate. As much as 92% of the economic growth variable can be explained by the general allocation fund (DAU), the regional tax, and the population.